Hypokalemia Improving the Investigation, Management and Therapeutics Monitoring of Hypokalemic Medical Inpatients at Tertiary Care Hospital A Clinical Audit - Muizz Zahoor, Saad Zahoor, Aisha Wazir, Shanza Ijaz, Saiqa Zahoor (Pakistan Journal of Medical & Health Sciences, 2023)
Background: One of the most frequent diseases in hospitalized individuals is Hypokalemia. it is more prevalent in individuals with underlying chronic conditions such as diabetes mellitus, heart failure, or chronic kidney disease (CKD). Objective: The objective of this audit was for improving the investigation, management and therapeutics monitoring of hypokalemic medical inpatients at tertiary care hospital. Methodology: The current clinical audit conducted at the department of cardiology, Hayatabad Medical complex Peshawar from January 2018 to December 2021. The audit covered all medical inpatients with hypokalemia during a one-week period. Prior to data collection, a daily list of medical inpatients with confirmed blood potassium levels of less than or equal to 3.4 mmol/L was obtained from the laboratory database in order to identify these individuals. After then, the patient’s records were found and examined to determine whether the patient had severe, moderate or mild, hypokalemia. Results: In the current clinical audit a total of 34 individuals were included in the pre-intervention group. The study found 26(76.4%) individuals with mild hypokalemia (3.1-3.4 mmol/L) & with significant hypokalemia (2.5-3.0 mmol/L) and only three individuals (8.8%) intended an ECG to check for cardiac arrhythmia. 14 (41.1%) participants had repeat U&E analysis after starting therapy. Only 7.5% (20%) of participants had their serum magnesium levels tested. Just eight (23.5%) individuals received proper treatment following conventional standards. Four weeks after the intervention, results were first gathered, and they revealed a significant improvement. Over all 32 individuals were included in the post-intervention group in which 21 were females and 11 were males. 15 participants (46.7%) had moderate hypokalemia (2.5–3.0 mmol/L), and 17 of them (53.2%) had mild hypokalemia (3.1–3.4 mmol/L). There were not any individuals found to have severe hypokalemia (<2.5) Conclusion: This audit significantly improved management by using a number of initiatives to raise knowledge and comprehension of the evaluations, care, and monitoring of the hypokalemic individuals. Keywords: Hypokalemia; Management; Therapeutics monitoring